2000
DOI: 10.1074/jbc.275.20.15226
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Neuronal Differentiation by p73 in a Neuroblastoma Cell Line

Abstract: The p53-related p73 and p63 genes encode proteins that share considerable structural and functional homology with p53. Despite similarities, their deletion in mice has different outcomes, implying that the three genes may play distinct roles in vivo. Here we show that endogenous p73 levels increase in neuroblastoma cells induced to differentiate by retinoic acid and that exogenously expressed p73, but not p53, is sufficient to induce both morphological (neurite outgrowth) and biochemical (expression of neurofi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
141
2
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(149 citation statements)
references
References 30 publications
5
141
2
1
Order By: Relevance
“…In contrast to mice lacking p53, p73-negative mice exhibit severe developmental defects, including hydrocephalus, hippocampal dysgenesis, chronic infections and inflammation, and abnormalities in the pheromone sensory pathway . This phenotype indicates that p73 plays a fundamental role in various developmental processes and it has been reported that p73 expression is triggered along neuronal, myogenic and hematopoietic differentiation (De Laurenzi et al, 2000;Fontemaggi et al, 2001).…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…In contrast to mice lacking p53, p73-negative mice exhibit severe developmental defects, including hydrocephalus, hippocampal dysgenesis, chronic infections and inflammation, and abnormalities in the pheromone sensory pathway . This phenotype indicates that p73 plays a fundamental role in various developmental processes and it has been reported that p73 expression is triggered along neuronal, myogenic and hematopoietic differentiation (De Laurenzi et al, 2000;Fontemaggi et al, 2001).…”
Section: Introductionmentioning
confidence: 64%
“…TAp73 expression is induced by cellular stress signals that partially overlap with activators of p53. In addition, the TAp73 promoter is activated by E2F1 and other proapoptotic genes such as adenoviral E1A and c-Myc, and during the course of cellular differentiation processes such as myogenic, hematopoietic and neuronal differentiation (De Laurenzi et al, 2000;Stiewe and Pu¨tzer, 2000;Fontemaggi et al, 2001;Zaika et al, 2001). Here, we have shown that induction of TAp73 expression by E2F1 triggers hTERT repression in H1299 cells.…”
Section: Regulation Of Htert By P73 M Beitzinger Et Almentioning
confidence: 99%
“…22 Both induction of endogenous p73 by ATRA as well as ectopic expression of TAp73 isoforms have been shown to induce morphological and biochemical markers of neuronal differentiation in N1E-115 neuroblastoma cells. 18 Here we show, that DNp73a efficiently blocks ATRA-induced differentiation of SH-SY5Y neuroblastoma cells. Whereas ATRA-treatment induced extension of multiple neurites as a morphological marker and expression of neurofilament as a biochemical marker of neuronal differentiation in mock cells, this was significantly reduced in DNp73a transfectants (Figure 1g and h).…”
mentioning
confidence: 57%
“…[16][17][18] Furthermore, exogenous expression of TAp73 is sufficient to induce morphological and biochemical markers of neuronal differentiation. 18 Whereas TAp73 enhances terminal differentiation of oligodendrocyte precursors, DNp73 inhibits this process.…”
mentioning
confidence: 99%
See 1 more Smart Citation